Pengembangan Media Pembelajaran Kimia Berbasis Android Untuk Penumbuhan Literasi Sains Siswa Pada Materi Reaksi Redoks Dan Elektrokimia - Harianto, Arifin; Suryati, Suryati; Khery, Yusran (IKIP Mataram, 2017)
The aims of this study were to produce android base chemistrylearning media prototype and evaluate its elibibility andeffectiveness on student science literacy growing on redox reactionand electrochemistry subject material. In form of research anddevelopment, this study was carried out by ADDIE (Analysis,Design, Development, Implementation, dan Evalution)model ofinstructional development. Data was collected by content anddesign validation questionnaire, practitioner and student respondquestionnaire, and science litracy test. Data was analyzed byelegiibility percentega and categories and N-gain test. Study resultshowed that media design and content validity was very eleigiblewith 80 % of eligibility percentage. Practitioner and studentsrespond was very eleigible with 82.22 % and 86.35 % of eligibilitypercentage average respectively. This media effectiveness onstudent literacy growing was proven by N-gain value 0.65 % withfair category. It can be concluded that android base chemistrylearning media that developed was very eligible for chemistylearning application and grow student science literacy on redoxreaction and electrochemistry subject material effectively.